(untitled) (Dermatology Reports, 2014)
Orofacial granulomatosis is a chronic granulomatous condition characterized by relapsing and remitting lip swelling and oral involvement that may include deep ulcers, tags and cobblestone formation. It occurs as an independent entity but also in conjunction with systemic diseases such as tuberculosis, sarcoidosis and Crohn’s disease. The clinical presentation is not indicative of concomitant systemic disease. To highlight the importance of thorough examination to rule out systemic disease, we present two childhood cases of orofacial granulomatosis, one of which was associated to Crohn’s disease.